Drunk bus [videorecording (DVD)] - Carlucci, John (Filmmaker); LaGanke, Brandon; Tahan, Charlie; Hayward, Kara, 1998-; Tangaroa, Pineapple (FilmRise, 2021)
Michael is a recent graduate whose post-college plan is derailed when his girlfriend leaves him for a job in New York City. When the bus service hires a security guard to watch over the night shift, Michael comes face to tattooed face with Pineapple, a 300-pound punk rock Samoan.